Subcutaneous Emphysema Following Chest Tube Insertion in a Patient with Secondary Spontaneous Pneumothorax Due to Chronic Obstructive Pulmonary Disease: A Case Report.: Tetra Arya Saputra, Adityo Wibowo - wibowo, adityo (Jurnal Kedokteran Universitas Lampung, 2025)
Pneumothorax, characterized by the accumulation of air in the pleural cavity and subsequent lung collapse, is a critical clinical entity with significant morbidity, particularly in patients with underlying chronic lung disease such as chronic obstructive pulmonary disease (COPD). Subcutaneous emphysema, although a recognized complication of chest tube insertion, can present diagnostic and management challenges, especially in patients with severe underlying lung disease. We report the case of a 71-year-old male with a history of moderate smoking and untreated COPD who presented with acute worsening dyspnea, pleuritic chest pain, and productive cough. The patient was initially diagnosed with an acute exacerbation of COPD and subsequently developed a left-sided secondary spontaneous pneumothorax, confirmed by chest radiography. Following chest tube insertion, the patient developed extensive subcutaneous emphysema, manifesting as palpable crepitus and swelling extending from the left chest to the neck and abdomen. This case highlights the importance of early recognition and management of pneumothorax and its potential complications in patients with pneumothorax. Subcutaneous emphysema following chest tube insertion can rapidly progress and compromise respiratory function. Awareness of risk factors and vigilant monitoring are essential to optimize outcomes in this vulnerable patient population.